2019
DOI: 10.1186/s13014-019-1226-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of postoperative radiotherapy in dermatofibrosarcoma protuberans: a propensity score-matched analysis

Abstract: ObjectiveThis study aimed to evaluate the role of postoperative radiotherapy (RT) in dermatofibrosarcoma protuberans (DFSP) and identify the prognostic factors influencing the disease-free survival (DFS).MethodsA total of 184 patients with DFSP were analyzed from 2000 to 2016. The regression model was used to examine the prognostic factors for DFS. Baseline covariates were balanced using a propensity score model. The role of RT was assessed by comparing the DFS of the surgery + RT group with that of the surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…The treatment, for DFSP of the breast, is based on surgery, whether primary or recurrent. The principal aim of surgery is to remove the tumor completely, because of the close relationship between residual tumor and local recurrence [ 41 43 ]. WLE is a very reasonable approach that has been widely used worldwide for DFSP of the breast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment, for DFSP of the breast, is based on surgery, whether primary or recurrent. The principal aim of surgery is to remove the tumor completely, because of the close relationship between residual tumor and local recurrence [ 41 43 ]. WLE is a very reasonable approach that has been widely used worldwide for DFSP of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that DFSP is a radioresponsive tumor [ 41 , 49 ]. For recurrent tumors or unresectable residual lesions, adjuvant radiotherapy is recommended in order to control the progression of disease [ 32 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with local recurrences were managed with repeated surgery with wide resection margins. Whenever anatomic or cosmetic difficulties to achieve adequate margins existed, postoperative RT [8] was given in an effort to improve local control and prevent unfavorable functional or cosmetic outcomes. Expectedly, distant recurrences were uncommon in our patients [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al [12] have shown that dermatofibromas have a higher proliferation index when compared to the superficial/peripheral portion of DFSP. Using 17% as the optimal cut-off point, Du et al [8] reported that patients with high Ki-67 expression had less favorable 5-year disease-free survival compared to those with expression levels. Our study is the first to analyze the Ki-67 index with respect to RFS as the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…A fibrosarcoma is a low-grade malignant tumor with a local recurrence rate of 60%[1]. The incidence of distant metastases is <1%[2,3].…”
Section: Introductionmentioning
confidence: 99%